Penerapan Video Animasi Sosialisasi Persyaratan dan Ketentuan Perjalanan dengan Kereta Api pada Masa Pandemi COVID-19 dengan Teknik Motion Graphic di PT. Kereta Api Indonesia (Persero) - Junaidi, Khofifah Aina; Yulian Mirza; Indarto (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
In order to reduce the positive number of COVID-19, there are several terms and conditions that must be met by prospective passengers before boarding the train. Therefore, PT. Kereta Api Indonesia (Persero) must socialize this information so that the general public knows about it. Motion graphic are one of the choices that attract the attention of many consumers because they present information that is not boring. The purpose of this study is to produce an animated video of the terms and conditions of travel by train during the COVID-19 pandemic using motion graphic techniques and providing this information to the public by sharing videos and video links that have been uploaded to social media. The research and development method used in this study is the Multimedia Development Life Cycle method, likert scale, validity and reliability test. This study produced a 5 minutes 30 seconds long video with .mp4 format. The respondents in this study were obtained from the dissemination of online questionnaires. The results of this study found that the attitude of 5 expert respondents is 94.5% in the